PENERAPAN BEBAN PEMBUKTIAN TERBALIK SEBAGAI ALTERNATIF PEMBERANTASAN TINDAK PIDANA KORUPSI MENUJU INDONESIA BEBAS KORUPSI - Misbakhul Munir; Machfudz Ali (Badan Penerbit STIEPARI Press, 2022)
This research applies the reverse burden of proof as an alternative to corruption-free eradication towards a corruption-free Indonesia. The criminal act of corruption is a big problem, because it can endanger the stability of the state and society's security, endanger social development, the community's economy, politics and even damage democratic and moral values ​​because it has become a culture and a threat to the ideals of a just and prosperous society. . The research method used in this research is non-doctrinal or empirical juridical. The research specifications are analytical descriptive, the approach used is an empirical juridical approach, so the data collected comes from primary data as the main data and secondary data as supporting data. To classify primary data, data collection is done in two ways, namely observation (observation) and interviews. using qualitative analysis method. The results of this study indicate that the model of applying the reverse burden of proof to corruption is carried out by asking or ordering the defendant to prove that his property was legally obtained, if the defendant cannot prove that the property was obtained not because of a criminal act of corruption, the property is deemed to have been obtained. also from corruption. The reverse burden of proof is an alternative that can be used by the prosecutor's office in uncovering and eradicating existing corruption cases.